Visionary Leadership: The Principal as a Driver of Quality Culture and Educational Innovation - Sobari, Muh.; Afgani , Muhammad Win; Afriantoni, Afriantoni (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
Improving quality has become increasingly important for educational institutions as an effort to achieve better control through their actions. The principal is a leader who holds the authority to manage all aspects within a school institution. In order for the duties and responsibilities of school leaders to be effectively realized, it is essential that principals understand, internalize, and apply several management concepts developed by thinkers in the business world namely, TQM (Total Quality Management), which is then applied in the field of education. The implementation of education must take into account the characteristics, aspirations, and needs of society. Education must be able to provide contextual responses in accordance with the global context. In other words, various efforts must be made to bring together stakeholders to ensure they have access to the policy formulation and decision-making processes, particularly regarding the equity and expansion of educational services, as well as the quality, relevance, and efficiency of educational management.